The impact of the German autobahn net on regional labor market performance: A study using historical instrument variables - Joachim Möller; Marcus Zierer (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
This paper analyzes the impact of the German autobahn net on the economic performance of German regions. To address endogeneity and reverse causation problems, we use historical instrument variables, i.e. a plan of the railroad net in 1890 and a plan of the autobahn net in 1937. We find a statistically and economically significant causal effect of transport infrastructure investments as measured by changes in the length of the autobahn net of West German NUTS 3 areas on regional employment and the wage bill.
Keywords: L91; N73; N74; R11; R40; R49; 330; Transport Infrastructure; Regional Labor Market; Performance; Historical Instrumental Variables; Reverse Causation; New Economic Geography